(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of theoretical and experimental studies on finding the optimal scheme of a cultivator for tillage in vineyards, providing high-quality tillage with minimal energy (power) consumption. The basic parameters of the machine and operational elements are substantiated.